Metabolic Insight Into the Neuroprotective Effect of Tao-He-Cheng-Qi (THCQ) Decoction on ICH Rats Using Untargeted Metabolomics - Yang, Rui-Pei; Cai, Da-Ke; Chen, Yu-Xing; Gang, Hai-Ning; Wei, Mei; Zhu, De-Quan; Li, Su-Mei; Yang, Jiu-Mei; Luo, Si-Ni; Bi, Xiao-Li; Sun, Dong-Mei (Frontiers in Pharmacology, 2021)
Tao-He-Cheng-Qi decoction (THCQ) is an effective traditional Chinese medicine used to treat intracerebral hemorrhage (ICH). This study was performed to investigate the possible neuroprotective effect of THCQ decoction on secondary brain damage in rats with intracerebral hemorrhage and to elucidate the potential mechanism based on a metabolomics approach. Sprague-Dawley (SD) rats were randomly divided into five groups: the sham group, collagenase-induced ICH model group, THCQ low-dose (THCQ-L)-treated group, THCQ moderate-dose (THCQ-M)-treated group, and THCQ high-dose (THCQ-H)-treated group. Following 3 days of treatment, behavioral changes, and histopathological lesions in the brain were estimated. Untargeted metabolomics analysis with multivariate statistics was performed by using ultra-high-performance liquid chromatography-mass spectrometry (UPLC-Q-Exactive Orbitrap MS). THCQ treatment at two dosages (7.56 and 15.12 g/kg·d) remarkably improved behavior (P < 0.05), brain water content (BMC), and hemorheology (P < 0.05) and improved brain nerve tissue pathology and inflammatory infiltration in ICH rats. Moreover, a metabolomic analysis demonstrated that the serum metabolic profiles of ICH patients were significantly different between the sham group and the ICH-induced model group. Twenty-seven biomarkers were identified that potentially predict the clinical benefits of THCQ decoction. Of these, 4 biomarkers were found to be THCQ-H group-specific, while others were shared between two clusters. These metabolites are mainly involved in amino acid metabolism and glutamate-mediated cell excitotoxicity, lipid metabo-lism-mediated oxidative stress, and mitochondrial dysfunction caused by energy metabolism dis-orders. In addition, a correlation analysis showed that the behavioral scores, brain water content, and hemorheology were correlated with the serum levels of metabolites derived from amino acid and lipid metabolism. In conclusion, the results indicate that THCQ decoction significantly attenuates ICH-induced secondary brain injury, which could be mediated by improving metabolic disorders in cerebral hemorrhage rats.